Solving the strength-ductility tradeoff in the medium-entropy NiCoCr alloy via interstitial strengthening of carbon. (March 2019) - Shang, Y.Y.; Wu, Y.; He, J.Y.; Zhu, X.Y.; Liu, S.F.; Huang, H.L.; An, K.; Chen, Y.; Jiang, S.H.; Wang, H.; Liu, X.J.; Lu, Z.P.
Abstract: Interstitial solid strengthening is an effective strategy to harden metallic materials, however, it usually deteriorates the ductility. Here, we report that addition of carbon into the medium-entropy NiCoCr alloy successfully enhances the strength at no expense of ductility. It was found that up to 0.75 at.% carbon was completely solid-solutionized in (NiCoCr)100-x Cx (x = 0, 0.10, 0.25, 0.50 and 0.75 at.%) without formation of any carbides. With the increase of carbon content from 0 to 0.75 at.%, the yield and fracture strength were increased from 242 to 347 MPa to 727 and 862 MPa, respectively, whilst the ductility kept as high as about 75%. It is noteworthy that the integral of the stress over strain for the alloy with 0.75 at.% carbon reaches a value of 59 GPa %, surmounting the level of many reported multi-principal elements alloys. Our analysis indicates that carbon addition increases stacking fault energy, thus delaying occurrence of twinning and decreasing the thickness of twin lamellas. At the early deformation stage, carbon decreases the stress localization and stimulates dislocation multiplication. After occurrence of deformation twinning, finer twinning structure in the alloys added with carbon not only can obstacle and trigger more dislocations, but also transfer plastic deformation more efficiently, thus promoting the twinning process, postponing the plastic instability and eventually giving rise to a more pronounced work-hardening. Our results not only have important implications for understanding the solid solution strengthening mechanism in medium-entropy alloys, but also shed lights on developing advanced metallic alloys with a unique combination of strength and ductility. Graphical abstract: Image 1 Highlights: Addition of carbon into NiCoCr simultaneously increase the strength and ductility. Carbon homogenizes the dislocation substructure and promotes uniform deformation. Carbon addition increases the stacking fault energy. Carbon addition delays occurrence of twinning and homogenizes plastic deformation.